How fresh is maple syrup? Sugar maple trees mobilize carbon stored several years previously during early springtime sap‐ascent. Issue 4 (7th December 2015) - Muhr, Jan; Messier, Christian; Delagrange, Sylvain; Trumbore, Susan; Xu, Xiaomei; Hartmann, Henrik
Summary: While trees store substantial amounts of nonstructural carbon (NSC) for later use, storage regulation and mobilization of stored NSC in long‐lived organisms like trees are still not well understood. At two different sites with sugar maple ( Acer saccharum ), we investigated ascending sap (sugar concentration, δ 13 C, Δ 14 C) as the mobilized component of stored stem NSC during early springtime. Using the bomb‐spike radiocarbon approach we were able to estimate the average time elapsed since the mobilized carbon (C) was originally fixed from the atmosphere and to infer the turnover time of stem storage. Sites differed in concentration dynamics and overall δ 13 C, indicating different growing conditions. The absence of temporal trends for δ 13 C and Δ 14 C indicated sugar mobilization from a well‐mixed pool with average Δ 14 C consistent with a mean turnover time (TT) of three to five years for this pool, with only minor differences between the sites. Sugar maple trees hence appear well buffered against single or even several years of negative plant C balance from environmental stress such as drought or repeated defoliation by insects. Manipulative investigations (e.g. starvation via girdling) combined with Δ 14 C measurements of this mobilized storage pool will provide further new insights into tree storage regulation and functioning. Abstract : See also the Commentary by Gessler and Treydte